2005
DOI: 10.1177/0011000004268636
|View full text |Cite
|
Sign up to set email alerts
|

Counselor and Client Predictors of the Initial Working Alliance:

Abstract: One mission of the International Forum section in The Counseling Psychologist is to increase the globalization of counseling psychology (Leong & Ponterotto, 2003). The goals of this study are in line with this mission: (a) to replicate U.S. counseling research on the working alliance to Taiwan by examining clients’perceptions of their counselors’ credibility and (b) to extend the working-alliance literature by examining the role that counselors’problem-solvingstyles play in predicting the initial working a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 50 publications
2
10
0
Order By: Relevance
“…The preference for pragmatic elements in therapy found in our study is also evident in the research (e.g., Wei and Heppner, 2005; Cao, 2008; Kuo et al, 2011). For instance, Cao (2008) found that Chinese college students were likely to be willing to stay in therapy and provide high ratings of therapist credibility when they perceived that therapy was directive and involved concrete and tangible techniques such as conveying information, probing for information, giving advice, directing behavior, and making interpretations.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The preference for pragmatic elements in therapy found in our study is also evident in the research (e.g., Wei and Heppner, 2005; Cao, 2008; Kuo et al, 2011). For instance, Cao (2008) found that Chinese college students were likely to be willing to stay in therapy and provide high ratings of therapist credibility when they perceived that therapy was directive and involved concrete and tangible techniques such as conveying information, probing for information, giving advice, directing behavior, and making interpretations.…”
Section: Discussionsupporting
confidence: 87%
“…Only four studies have specifically explored effective therapeutic approaches with Chinese clients (i.e., Lin, 2001; Wei and Heppner, 2005; Cao, 2008; Kuo et al, 2011), and these studies have significant limitations. They are often based on experts’ self-reports or interpretations of data through theories and concepts in the field of psychotherapy in the west.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the many benefits of the working alliance and its consistent influence on therapeutic outcomes, fostering and maintaining the working alliance is viewed as a crucial aspect of the therapy. Research has begun to examine the individual factors that predict alliance strength, such as a client's willingness to seek help (Calsyn, Morse, & Lemming, 2006) and the therapist's perceived credibility (Wei & Heppner, 2005). Given the well-documented relationship between the working alliance and therapy outcome, individuals who experience difficulty forming or maintaining a working alliance may be at a considerable disadvantage in therapy.…”
mentioning
confidence: 99%